Grandchildren of grandparents with Alzheimer's disease: Exploratory study of the impact of the disease on their relationships. (May 2023) - Megido, Maria Jesus; Celdrán, Montserrat; Ferrer, Assumpta; Roca, Montserrat; Pujol-Ribera, Enriqueta; Zabaleta-del-Olmo, Edurne
The aim of this study was to describe the perception of changes that Alzheimer's disease in grandparents has made to the relationship with their grandchildren of between 6 and 13. Qualitative methodology was used. Semi-structured interviews were carried out with 25 grandchildren living in Catalonia, Spain. Participants reported a change in roles from being the care receiver to being the caregiver, changes in the activities that they did together and a positive impact on the grandparent's emotional wellbeing. In the physical sphere, sleeping problems were reported in grandchildren that cohabited with their grandparents. The feelings they described include fear of not being recognized by their grandparents and sadness, as well as satisfaction resulting from their affection and participating in caring. These findings suggest the need to provide information and resources for grandchildren and their families to enable them to deal with the disease.